Hadith #4098 - Sahih Muslim - Talha bin 'Abdul Malik طلحة بن عبد الملك الأيلي (Sahih Muslim)
I asked ‘Abdullah b. Abu Aufa whether Allah’s Messenger (ﷺ) had made any will (in regard to his property). He said: NO. I said: Then why has making of will been made necessary for the Muslims, or why were they commanded to make will? Thereupon he said: He made the will according to the Book of Allah, the Exalted and Majestic.
Grade: Sahih